Sărada Mahinda = Jan̲ātipati Mahinta Rājapakṣa = President Mahinda Rajapakse. (Ministry of Mass Media & Information, 2011)
A collection of cartoons on Mahinda Rajapakse's first five year as Sri Lanka's president.